2008
DOI: 10.1111/j.1439-0388.2008.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the porcine Kisspeptins receptor gene and evaluation as candidate for timing of puberty in sows

Abstract: Kisspeptins receptor (KISS1R), also called GPR54, is a key regulator of puberty in many species. KISS1R and its genetics in pigs remain unexplored. The objective of this study was to characterize the porcine KISS1R gene and evaluate the association of KISS1R mutations with age at puberty in sows. KISS1R was assigned to pig chromosome 2q21-24 by radiation hybrid mapping. It has a 1438 bp full-length cDNA and spans 3349 bp genomic sequence consisting of five exons and four introns. Semi-quantitative RT-PCR showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
(52 reference statements)
1
23
0
Order By: Relevance
“…Recently, Lents et al [17] reported that central and peripheral administration of the full length of human kisspeptin effectively stimulates LH and FSH release in prepubertal gilts. Further, porcine kisspeptin receptor GPR54 was identified with an abundant expression in the hypothalamus [28]. Taken together with the current result, PeN kisspeptin neurons may be responsible for positive feedback action of estrogen to induce a preovulatory GnRH/LH surge.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, Lents et al [17] reported that central and peripheral administration of the full length of human kisspeptin effectively stimulates LH and FSH release in prepubertal gilts. Further, porcine kisspeptin receptor GPR54 was identified with an abundant expression in the hypothalamus [28]. Taken together with the current result, PeN kisspeptin neurons may be responsible for positive feedback action of estrogen to induce a preovulatory GnRH/LH surge.…”
Section: Discussionsupporting
confidence: 56%
“…The mutation positions were based on the mRNA and amino acid sequence of Bos Taurus GPR54 (XM 607130 and XP 607130 respectively). In general, GPR54 gene showed abundant polymorphism, mutations were also found in human (11,12) and pig (13).…”
Section: Resultsmentioning
confidence: 98%
“…Kiss1r mRNA has been detected in the hypothalamus of pig (Li et al, 2008) and monkey (Shahab et al, 2005) and the pituitary of sheep (Smith et al, 2008). There has been recent interest in conservation of the kisspeptin regulation of reproduction during evolution and in keeping with this the kisspeptin receptor has been detected in several fish species, notably in the brain (Parhar et Biran et al, 2008;Filby et al, 2008;van Aerle et al, 2008;Carrillo et al, 2009;Li et al, 2009;Mechaly et al, 2009;Yang et al, 2010) and in frog Moon et al, 2009).…”
Section: Other Speciesmentioning
confidence: 98%